Basic economics - Trenton, Rudolph W. (New Jersey : Prentice-Hall, 1978)
Economics is everybody's business. Without becoming specialists in this field, we need a working knowledge about the operations of our economy. We learn to read and write in school without regard to our future occupation in life. The use of economic information is equally common to everyday life. The housewife goes to the store to de her shopping, her husband gets his do-it-yourself kit, but both are only partially aware that they are making economic decisions. Some decisions are made by habit or instinct; we can buy the blue package rather than the green one without finding out what it contains, and we discover at home, regretfully, that we bought apricots instead of peaches. Important economic decisions are sometimes made with no more thought. A man buys a life insurance policy with an obligation to pay a premium for the next twenty years without ever reading the fine print. He does it because the salesman is a nice fellow who invites him for a drink and tells good stories. A newlywed couple contract to build a house in a suburban development because the bride enjoyed the sunset when the realtor drove them out to show the lot. The unhappy results that can follow such impulsive actions show that a hunch is no longer a satisfactory substitute for economic information.
Part I. AN OVER-ALL LOOK AT OUR ECONOMIC SYSTEM -- 1. The Modern Economy -- 2. The Free Enterprise Economy -- 3. Government in the American Economy -- Part II. PRICES AND THEIR APPLICATION -- 4. Production -- 5. Business -- 6. Price -- 7. Competition -- 8. Monopoly Control -- 9. Risk and Security -- 10. On Human Effort -- 11. Agriculture -- 12. Consumption -- Part III. MONEY, INCOME, AND ECONOMIC GROWTH -- 13. Money -- 14. Financial Institutions -- 15. The Nation's Income -- 16.Business Fluctuations and Economic Growth -- 17. Public Finance -- 18. Monetary and Fiscal Policy -- Part IV. THE UNITED STATES AND THE WORLD ECONOMY -- 19. International Payments -- 20.Foreign Trade -- 21. Economic Development -- 22. Russia and the West.
Includes bibliographical references and index.
Keywords: ECONOMICS